Frontispiece: (View 1/2021). Issue 1 (6th February 2021) - Unknown
Abstract : Scientific and technological innovation occupies an extremely important place in the history of human medical development. In terms of the control and innovation of cutting‐edge IVD technologies, Beckman Coulter has established a solid foundation, leading the entire industry from manual work to automation and intellectualization. Throughout the company's scientific and technological innovation chronicle, the spirit of innovation and exploration by Dr. Beckman and the Coulter brothers has been inherited and persisted in the new generation. In the future, Beckman Coulter will continue to invest in clinical value, lean management, smart solutions, golden services and other aspects, adhering to tradition, leading the industry with innovation, and setting a benchmark with quality.